2012
DOI: 10.1007/s00280-012-1868-0
|View full text |Cite|
|
Sign up to set email alerts
|

The “survivin suppressants” NSC 80467 and YM155 induce a DNA damage response

Abstract: These data provide the first evidence that NSC80467 and YM155 are DNA damaging agents where suppression of survivin is a secondary event, likely a consequence of transcriptional repression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 15 publications
10
103
2
1
Order By: Relevance
“…Recent findings have shown that the uptake of YM155 into cells was dependent on the presence of a specific solute carrier SLC35F2 and it is conceivable that varying levels of this transporter on the outer membrane surfaces of tumoral cells could have moderated the cytotoxicity of YM155 [28]. Various reports have since questioned if the suppression of survivin is the sole and main effect of YM155-induced cytotoxicity [21,26,28]. The consensus is that YM155 is a DNA intercalating agent and induces a DNA damage response that leads to apoptotic cell death.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Recent findings have shown that the uptake of YM155 into cells was dependent on the presence of a specific solute carrier SLC35F2 and it is conceivable that varying levels of this transporter on the outer membrane surfaces of tumoral cells could have moderated the cytotoxicity of YM155 [28]. Various reports have since questioned if the suppression of survivin is the sole and main effect of YM155-induced cytotoxicity [21,26,28]. The consensus is that YM155 is a DNA intercalating agent and induces a DNA damage response that leads to apoptotic cell death.…”
Section: Discussionmentioning
confidence: 97%
“…YM155 was reported to intercalate with DNA and to induce a DNA damage response which is purportedly central to its anticancer properties [26,28]. In the presence of YM155, prostate cancer cells PC3 showed dose dependent increases in two biomarkers of DNA damage, phosphorylated histone gH2AX and phosphorylated KAP1.…”
Section: Formation Of Gh2ax In Treated Cellsmentioning
confidence: 98%
See 2 more Smart Citations
“…Glaros and colleagues first reported that YM155 was a DNA damaging agent rather than a transcriptional suppressor of survivin , because the concentrations of YM155 required to induce γH2AX and P-KAP1, two hallmarkers of DNA damage response, were much lower than that needed to inhibit survivin [49]. YM155-induced downregulation of survivin was likely a secondary event following DNA damage.…”
Section: Discussionmentioning
confidence: 99%